Effect of removal organic sulfur from coal macromolecular on the properties of high organic sulfur coal. (1st January 2020) - Tang, Longfei; Chen, Songjiang; Gui, Dongjiao; Zhu, Xiangnan; He, Huan; Tao, Xiuxiang
Highlights: Basic aromatics in coal macromolecular structure changed little after removing 60% organic sulfur. Low molecular weight fragments produced by branched chain breakage changed coal thermal characteristics. Contents of carbon-containing groups were changed by reduction effect of assistants. Side reactions of reducing desulfurization led to the increase of oxygen-containing groups. Abstract: The present work investigated the effect of efficient reduction desulfurization method (potassium tertbutoxide and hydrosilane system) on coal properties. Characteristic changes of high organic sulfur coal were studied utilizing TGA, FTIR and XPS after desulfurization. Results showed that more than 60% organic sulfur was removed, while the calorific value of coal samples decreased slightly and the aromatics in coal macromolecular structure were destroyed little. After treatment, formation of low molecular fragments from aliphatic carbons leaded to the increase of mass loss in TGA. XPS results revealed that some oxygen-containing groups were deoxidized after reduction treatment. The changes of coal properties were mainly attributed to the fracture of branch chain, the reduction of oxidized carbon atoms and side reactions during reduction desulfurization.